Anthropological Landscapes in the Literature of the Age of Enlightenment - Nickel, Beatrice (The international journal of literary humanities, 2025)
In the literature of the Enlightenment, landscapes played a crucial role. These did not present an end in themselves but served an imaginative clarification of the idea of man. Among the anthropological landscapes in eighteenth-century literature, the Polynesian island Tahiti stood out in particular, since it was imagined as an earthly paradise: Tahitians were said to be in a permanent state of perfect bliss guaranteed above all by free sexuality. Louis-Antoine de Bougainville declared the Tahitians to be the embodiment of the homme naturel in his travelogue entitled Voyage autour du monde par la frégate du roi La Boudeuse et la flûte L’Étoile en 1766, 1767, 1768, et 1769 (1771) as a means of social criticism. Tahiti thus moved to the center of the contemporary debate about the relationship between the state of nature and the civil society. The islanders’ natural way of life was imagined as a positive counter-image to depraved European civilizations. The article highlights which anthropological goals the literary imaginations of Tahiti served.